2010
DOI: 10.3109/14767058.2010.482608
|View full text |Cite
|
Sign up to set email alerts
|

Fetal pulmonary vascular remodeling in a rat model induced by hypoxia and indomethacin

Abstract: Hypoxia and indomethacin had synergistic effect on fetal pulmonary vascular remodeling. This rat model induced by combined treatments can mimic human persistent pulmonary hypertension of the newborn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…Female Sprague-Dawley rats weighing 250-300 g were mated overnight (day 0 of gestation). The rat model of PPHN was induced by hypoxia and indomethacin [7]. In brief, on day 19 of gestation, pregnant rats were treated with both hypoxia (oxygen concentration, 12%) and indomethacin (0.5 mg/kg; I7378; Sigma-Aldrich, St Louis, Missouri, USA).…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Female Sprague-Dawley rats weighing 250-300 g were mated overnight (day 0 of gestation). The rat model of PPHN was induced by hypoxia and indomethacin [7]. In brief, on day 19 of gestation, pregnant rats were treated with both hypoxia (oxygen concentration, 12%) and indomethacin (0.5 mg/kg; I7378; Sigma-Aldrich, St Louis, Missouri, USA).…”
Section: Animalsmentioning
confidence: 99%
“…There is more and more evidence that the levels of eNOS are conspicuously associated with PPHN [4][5][6]. In our previous rat model of PPHN induced by hypoxia and indomethacin, eNOS expression of lung tissue was significantly upregulated [7].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…72 In our rat model of PPHN induced by hypoxia and indomethacin, eNOS expression in the endothelial cells is also significantly upregulated. 73 The eNOS gene is composed of 26 exons spanning approximately 21 Kb of genomic DNA on chromosome 7q35-36, and its promoter shares many features with other endothelial-specific promoters including Ets, GATA, Sp1 and other cis-regulatory elements that are required for their basal expression. 68 In normal conditions, eNOS expression is highly restricted to vascular endothelial cells.…”
Section: Pphn and Enosmentioning
confidence: 99%
“…78,79 In our rat model for PPHN, the levels of eNOS mRNA and protein expression were significantly upregulated. 73 To better understand eNOS gene regulation in endothelial cells, we isolated pulmonary vascular endothelial cells via magnetic-activated cell sorting. We found that there was a hypomethylation trend in CpG sites in the rat eNOS core promoter from pulmonary vascular endothelial cells of PPHN, but there was no statistically significant difference compared with control.…”
Section: Pphn and Enosmentioning
confidence: 99%